2008
DOI: 10.3201/eid1406.071270
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A Virus (H3N8) in Dogs with Respiratory Disease, Florida

Abstract: Genetic and antigenic characterization established the uniqueness of this virus circulating in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
229
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 162 publications
(230 citation statements)
references
References 17 publications
1
229
0
Order By: Relevance
“…Phylogenetic analysis of 4 Greyhound isolates and 2 pet dog isolates revealed that these viruses were closely related to EIV strains recovered from horses since 2000, belonging to the Florida sublineage of the American lineage of H3N8 EIV. 2,11 The isolation of 4 closely related H3N8 EIV subtype strains from dogs that died in different locations over a 2-year period, together with serologic evidence of widespread infection among Greyhounds in different states, strongly confirmed sustained circulation of CIV involving dog-to-dog transmission of the virus. 2,11,18 Most outbreaks of CI occur in rescued, kenneled, or boarded dogs.…”
mentioning
confidence: 91%
See 4 more Smart Citations
“…Phylogenetic analysis of 4 Greyhound isolates and 2 pet dog isolates revealed that these viruses were closely related to EIV strains recovered from horses since 2000, belonging to the Florida sublineage of the American lineage of H3N8 EIV. 2,11 The isolation of 4 closely related H3N8 EIV subtype strains from dogs that died in different locations over a 2-year period, together with serologic evidence of widespread infection among Greyhounds in different states, strongly confirmed sustained circulation of CIV involving dog-to-dog transmission of the virus. 2,11,18 Most outbreaks of CI occur in rescued, kenneled, or boarded dogs.…”
mentioning
confidence: 91%
“…2,11 The isolation of 4 closely related H3N8 EIV subtype strains from dogs that died in different locations over a 2-year period, together with serologic evidence of widespread infection among Greyhounds in different states, strongly confirmed sustained circulation of CIV involving dog-to-dog transmission of the virus. 2,11,18 Most outbreaks of CI occur in rescued, kenneled, or boarded dogs. 4 Clinical signs of the disease include low-grade fever, lethargy, anorexia, nasal discharge, and prolonged cough.…”
mentioning
confidence: 91%
See 3 more Smart Citations